THE INFLUENCE OF PRICE AND PROMOTION ON PURCHASE DECISIONS AT KOPI SHOP DALAM GANG, JAKARTA - Niken Herawati; Ade Sri Mulyani; Asrah Tandirerung Ranteallo (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
In the increasingly competitive coffee shop market, consistency and quality are the most important things for every coffee shop that wants to avoid the trap of early failure, especially coffee and customer service, including those related to price and promotion. The purpose of this study is to determine the effect of price and promotion on purchasing decisions at Kedai Kopi Dalam Gang Jakarta. This type of research is a statistical quantitative study with a sampling technique using probability sampling, with a total of 80 respondents. Primary data in this study were collected by distributing questionnaires, and secondary data obtained from books, journals and internet media. The data analysis techniques used are multiple linear regression analysis methods, classical assumption tests, instrument tests (validity and reliability), hypothesis testing, and coefficient of determination using the SPSS program version 25.0. The results of this study indicate that partially, each variable, namely price and promotion, has a positive and significant effect on purchasing decisions at Kedai Kopi Dalam Gang Jakarta, which is 74.6%, and the remaining 25.4% is influenced by other factors outside of it.